Experimental Roman Minting: Casting Silver-Copper Alloys into a Bronze Mould - Nicola George (EXARC Journal)
This paper provides the details of a Roman minting experiment, which used a bronze mould to cast debased silver blanks typical of the third century A.D. The investigation follows the paper ''Experiments reproducing Roman debased alloys" (George, 2020) which studied the manufacturing methods used in the production of Roman silver coinage. The purpose of those experiments was to both recreate the casting process used by ancient moneyers and test the suitability of different mould materials, including clay, limestone and bronze. Although the experimental moulds offered new insights into minting technologies, the initial bronze mould experiments failed to produce blanks with a silver content lower than 70 %. Upon reflection, this was caused by decisions made in the design process, such as the choice of coating agent, which negatively affected the success of the castings. The current investigation revisits the bronze mould experiments using a different release agent. and results of the second bronze mould experiment are presented here.